The Patterns and Influences of Women's Legislative in Simultaneously General Elections in Indonesia - Asmar, Abd. Rais; Nurdin, Reskiyanti; Arbani, Tri Suhendra; Syam, Febrianto; Fuady, Muhammad Ikram Nur; Lukita, Fauzi Hadi (International Journal of Criminology and Sociology, 2021)
Gender is one of the essential aspects of the democratic process, including in the legislative elections. In this regard, this study aims to see the implementation of recruitment patterns and the influences used by women, and the factors that win women in Indonesia's legislative elections. This research is qualitative research by carrying out the documentation at the General Election Commission Office and in-depth interviews with women legislators elected in the 2019 general elections. The results showed that the Indonesian government has implemented affirmative action well, indicated by a minimum quota of 30% for female legislators. Besides, affirmative action's success is also supported by recruiting legislative candidates by parties using several approaches, namely the oligarchic approach, the cadre selection approach, the structural approach, the transparency approach, and the dedicated approach. Furthermore, the prevalence and factors that support women legislators' success in the 2019 elections, which have increased compared to the 2014 elections, influence the sequence number and the incumbent candidates' influence. In the end, this affirmative action policy positively affects women who want to take part in politics.